Arborização planejada: instrumento para construção de municípios sustentáveis e resilientes - Silva, Rodrigo Fernandes da (2021)
This study seeks to identify the presence/absence of the PDAU – Master Plan for Urban Afforestation in the municipalities of the micro-region of Marechal Cândido Rondon, west of the State of Paraná. Its general objective was to study the practice of afforestation as a healthy and necessary planning action, which can result in actions in favor of sustainable development. The study shows the analysis of the questionnaires, carried out by 30 participants, from 7 municipalities belonging to the micro-region of Marechal Cândido Rondon, Entre Rios do Oeste, Marechal Cândido Rondon, Mercedes, Nova Santa Rosa, Palotina e Pato Bragado e Quatro Pontes presenting their characterization, their education, area of operation, the existence or not of master plans and director plans for urban afforestation and knowledge about the specific theme, urban afforestation, its conditions and its benefits for the improvement of people's quality of life. The study counted on the participation of 30 professionals linked to the secretariats and departments of the environment or spaces of environmental management of the city halls of the Marechal Cândido Rondon micro-region. The study showed that all participating municipalities have their master plan and only two have the urban afforestation plan, which disagrees with the state legislation that provides for its creation and implementation in all municipalities in the State of Paraná. Likewise, there is a lack of professionals with specific training in most of the environmental management teams in the participating municipalities, as only a few have a professional with higher education to work in this area. It is evident during the study that the professionals who carry out environmental management, participating in the study, do not have a record of updated information about their municipalities It is evidenced that both technicians and the population in general have a great need for knowledge and understanding about the benefits of urban afforestation to improve the quality of life of its inhabitants.